Short-term Quality of Life After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy - Özgül Düzgün; İnanç Şamil Sarıcı; Serkan Gökçay (İstanbul Medical Journal, 2018)

(untitled)
Introduction: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) have been increasingly performed in many advanced centers of our country. Short-term quality of life (QoL) after the CRS with HIPEC was investigated in Turkish population. The purpose of our study was to investigate the QoL in patients operated for peritoneal carcinomatosis (PC).Methods: Retrospectively collected data from 42 consecutive patients, who had undergone CRS and HIPEC, and 92 abdominal malignancy patients after oncological surgery without CRS and HIPEC were selected in the study between 2012 and 2015. A Turkish version of the European Organization for Research and Treatment of Cancer questionnaire (QLQ-C30) was used at the 6th month following surgery for the QoL assessment. Statistical analysis was done with one sample t-test, and p<0.05 was accepted as statistically significant.Results: In total, 42 CRS+HIPEC patients were analyzed; of which, 30 (71.4%) were female and 12 (28.5%) were male. The median age was 52 years (range, 22-69). CRS with HIPEC was performed for colorectal carcinoma in 15 patients (35.7%), ovarian cancer in 12 patients (28.5%), gastric cancer in 6 patients (14.2%), pseudomixsoma peritonei in 3 patients (7.1%), sarcoma in 3 patients (7.1%), and mesenchymal tumor in 3 patients (7.1%). The median intraoperative peritoneal carcinomatosis index score was 15 (6-29), whereas the completeness of the cytoreductive score was 0 and 1. The median follow-up period for all patients was 12 months (range, 6-22 months). The functional and symptom scores were equal between the CRS with HIPEC and without CRS+HIPEC cancer patients (p>0.05).Conclusion: Short-term QoL after the CRS with HIPEC patients and without the CRS+HIPEC oncologic patients is found to be similar in Turkish population.